Genotype Assignment of Haemophilia A by Use of Intragenic and Extragenic Restriction Fragment Length Polymorphisms - Bröcker-Vriends, A H J T; Briët, E; Quadt, R; Dreesen, J C F M; Bakker, E; Claassen-Tegelaar, R; Kanhai, H H H; van de Kamp, J J P; Pearson, P L (Thrombosis and Haemostasis, 1987)
We performed DNA analysis in 20 families with haemophilia A in order to evaluate its usefulness for carrier detection and prenatal diagnosis.The polymorphic Bell site within intron 18 of the factor VIII gene and the extragenic TaqI and Bglll polymorphic sites which are detected by the random DNA probes designated St 14 and DX13, respectively, were investigated for.Two events of recombination were found between the St 14 and the haemophilia A locus in 51 informative meioses. In one of these recombinant meioses crossing over had also occurred between the DX13 and the haemophilia A locus. No further crossovers between the DX13 and the haemophilia A locus were found in 20 informative meioses.Segregation analysis of the polymorphic markers and the deleterious mutation within the families allowed a diagnosis at the gene level for 52 out of 57 potential carriers. The new method considerably decreased the uncertainty about carriership for seventeen of the nineteen women with a probability of carriership between 5% and 95% based on pedigree analysis and factor VIII assays.In seven cases chromosome and DNA analysis of a chorionic villus biopsy was carried out. Three of the fetuses were female, four were male. Three of the male fetuses had inherited the normal maternal X-chromosome and were, therefore, not affected. For another male fetus no diagnosis at the gene level was possible since the mother was homozygous for all the known restriction fragment length polymorphisms within or closely linked with the haemophilia A locus.
Keywords: Carrier detection; Haemophilia A; Prenatal diagnosis; Restriction fragment length polymorphisms